Macrozoobenthic Community in Different Mangrove Condition: Relation with Chemical-Physical Sediment Characteristics (Torani Journal of Fisheries and Marine Science, 2018)
The existence of mangrove in coast areas have both ecologic and physical important functions.  Mangrove is a high productive ecosystem. Litters from fallen leaves and twigs are organic sources for macrozoobenthic life.  The aim of this research was to determine the response of macrozoobenthics on total organic matter content and other chemical-physico characters of sediments due to differences in mangrove conditions. This research was conducted from May to September 2016 in Sub-district of Ampallas, Distric of Mamuju, Province of West Sulawesi, Indonesia. Sediments in 20 cm2 transects were collected using small shovel to obtain the macrozoobenthic samples. The sediments contained macrozoobenthics were sieved using a 1 mm mesh size sieve net. Four sampling sites were chosen, each to represent areas with no mangroves, low, medium, and high densities.  The total of organic matter samples were collected using 2 inch diameter of PVC pipe cores, which were analyzed further using Loss by Ignition method.  Besides total of organic matter, several parameters (i.e. redox potential, sediment pH, salinity, temperature, and dissolved oxygen) were measured.  The results showed that gastropods dominated the existed macrozoobenthics.  Gastropods and oligochaete lived in greater amounts in high mangrove density site with higher organic matter content and fine substrate.Keywords: mangroves, macrozoobenthics, organic matter, Distric of Mamuju